Cardiac mortality is associated with low levels of omega-3 and omega-6 fatty acids in the heart of cadavers with a history of coronary heart disease. - Nipon Chattipakorn (2018)
The benefits of omega-3 (ie, eicosapentaenoic acid and docosahexaenoic acid [DHA]) and omega-6 (ie, linoleic acid and arachidonic acid [AA]) fatty acids on reducing cardiac mortality are still debated. In this study, we tested the hypothesis that high levels of omega-3 and omega-6 fatty acids in heart tissues are associated with low cardiac mortality in Thai cadavers. One hundred fresh cadavers were examined in this study. The cause of death, history of coronary heart disease (CHD), and fish consumption habits were obtained from death certificates, cadaver medical record profiles, and a questionnaire to a person who lived with the subject before death. In each cadaver, biopsies of cardiac tissues were taken from the interventricular septum for measurement of fatty acid. Of the 100 cadavers (average age, 69 +/- 13 years), 60 were men. The frequency of fish consumption was directly associated with omega-3 and omega-6 fatty acids in heart tissues (P < .01). History of CHD and cause of death (cardiac vs noncardiac) were not significantly associated with levels of omega-3 or omega-6 fatty acids. However, in cadavers with a history of CHD, high levels of omega-3 and omega-6, particularly DHA and AA, were associated with low cardiac mortality (P < .05). Fish consumption is associated with levels of omega-3 and omega-6 fatty acids in heart tissues. Although omega-3 and omega-6 fatty acids are not associated with cardiac mortality in the overall studied population, their low levels (especially DHA and AA) in heart tissues are associated with high cardiac mortality in cadavers with a history of CHD.